PENGARUH SELF AWARENESS TERHADAP PERKEMBANGAN KARAKTER SISWA KELAS X MA CIKANDE KABUPATEN BANDUNG BARAT - Yeni Siti Rokayah; Siti Hodijah; Lili Halimah (LPPM Universitas Cipta Mandiri, 2025)
The purpose of this study is to determine the influence of self-awareness on the character development of grade X students at Madrasaha Aliyah (MA) Cikande. This research is motivated by the importance of self-awareness as a foundation in character building, especially in facing social and moral challenges among adolescents today. The study used a qualitative approach by applying the survey method to 33 respondents. Data collection was conducted using a closed-ended questionnaire with a 5-point likert scale. The statement is prepared based on indicators of self-awareness according to Daniel Goleman and character development based on Thomas Lickona's theory. Data analysis was carried out through normality tests, Pearson correlations, and simple linear regression. The results of the analysis showed that self awareness had a positive and significant effect on the development of students' character, with a determination coefficient value (R²) of 0.419 and a Pearson correlation value of 0.648 (p < 0.01). These findings show that the higher the level of self-awareness of students, the higher the level of their character development. Therefore, strengthening self-awareness needs to be an integral part of the character education strategy in the secondary school environment.